THE INFLUENCE OF COMPUTERS ON CREATIVE INDUSTRIES AND THE DEVELOPMENT OF DIGITAL ART - Arfan Utiarahman; Novianty Djafri; Mardia Bin Smith (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
Computers have revolutionised the creative industry and digital art by introducing sophisticated software and hardware, such as Adobe Creative Suite and graphic tablets, which allow artists to create works of high quality and incredible detail. New technologies such as virtual reality (VR) and augmented reality (AR) have transformed the interaction between artists and artworks, enabling creation in three-dimensional spaces and more immersive interactive experiences. In addition, networking and cloud technologies facilitate global collaboration and efficiency in art production, while innovations such as blockchain and NFTs offer new ways to distribute and protect digital artworks. This combination of advanced tools, technologies and educational resources is fuelling rapid growth and transformation in the digital art world.